Non-linear unit-hydrograph runoff routing based on kinematic wave theory - Goi, Soon Luan. (2009)
A simple method of flood hydrograph synthesis. the kinematic wave "unit hydrograph" (KWUH) method, based on the kinematic wave theory, had been proposed by Lee et al (1992). The method is able to capture the unit response hydrograph of a catchment explicitly in terms of three characteristic, catchment-averaged, physically meaningful parameters. The parameters are the length L, roughness N and slope S associated with a rectangular overland flow plane. However, the KWUH method has not been tested on any observed streamflow data and the relationships between the three parameters and their corresponding catchment characteristics have not been defined.